Упростите выражение: 1) (1+√5)²;2) (√5-√3)(√5+√3);3) (3√14+√7):√7-2√2

0 голосов
30 просмотров

Упростите выражение: 1) (1+√5)²;2) (√5-√3)(√5+√3);3) (3√14+√7):√7-2√2


спросил от (15 баллов) в категории Алгебра
2 Ответы
0 голосов
 
Лучший ответ

.....................................

ответил от Легенда (80.5 тыс. баллов)
0 голосов

1) (1+√5)²=1+2*√5+5;
2) (√5-√3)(√5+√3)=5-3=2;
3) (3√14+√7):√7-2√2=
(3√7*√2+√7):√7-2√2=√7*(3*√2+1):√7-2*√2=(3*√2+1)-2*√2=1+√2.

ответил от Академик (71.3 тыс. баллов)
...